Prediksi Lendutan Akibat Bond Slip Pada Dinding Beton Bertulang [Prediction of Deflection Due to Bond Slip on Reinforced Concrete Walls] - Bali, Ika; Sadikin, Sadikin (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2017)
Deflection occurs on reinforced concrete wall when it reaches the ultimate strength can be contributed by the deflection due to bending, shear and bond slip. The bond slip occurs when the loss of bond between concrete and steel reinforcement, causing the stress distribution becomes disturbed. This generates an additional deflection on the walls of reinforced concrete. This analysis study was conducted to predict the additional deflection due to the bond slip on reinforced concrete walls that were subjected to lateral load at the ultimate strength condition of the walls. The deflection due to bond slip at the ultimate strength condition of the walls is estimated by the strength-of-material concept. The wall ultimate strength is determined as the minimum of flexural and shear strengths that based on a strength-of-material concept, and the shear strength and the Softened strut-and-tie model, respectively. The specimens of reinforced concrete walls used in this study are the reinforced concrete walls with a single curvature that available in the literature. The results of this study indicated that the deflection due to bond slip provides the additional deflection average of 5.5% of the total deflection due to bending and shear as the wall reaches the ultimate strength. This study shows that the effect of deflection due to bond slip is smaller than the deflection due to shear and bending.BAHASA INDONESIA ABSTRAK: Lendutan terjadi pada dinding beton bertulang saat mencapai kekuatan batas dapat dikontribusikan oleh lendutan akibat lentur, geser dan bond slip. Bond slip terjadi ketika hilangnya ikatan antara beton dan baja tulangan, menyebabkan distribusi tegangan menjadi terganggu. Hal ini menghasilkan lendutan tambahan pada dinding beton bertulang. Studi analisis ini dilakukan untuk memprediksi lendutan tambahan akibat bond slip pada dinding beton bertulang yang mengalami beban lateral pada kondisi kekuatan batas dinding. Lendutan akibat bond slip pada kondisi kekuatan batas dinding diestimasi dengan konsep kekuatan material. Kekuatan batas dinding ditentukan berdasarkan minimum dari kekuatan lentur dan geser yang berturut-turut didasarkan pada konsep kekuatan material dan model Softened strut-and-tie. Spesimen dari dinding beton bertulang yang digunakan dalam penelitian ini adalah dinding beton bertulang dengan kelengkungan tunggal yang tersedia dalam literatur. Hasil penelitian ini menunjukkan bahwa lendutan akibat bond slip memberikan rata-rata lendutan tambahan 5,5% dari total lendutan akibat lentur dan geser saat dinding mencapai kekuatan batas. Studi ini menunjukkan bahwa pengaruh lendutan akibat bond slip lebih kecil dari pada lendutan akibat geser dan lentur.